New enantioselective synthesis of (S)-2-ethoxy-3-(4-hydroxyphenyl)Propanoic acid esters (EEHP and IEHP), useful pharmaceutical intermediates of PPAR agonists - Mujahid, Mohammad; Kunte, S. S.; Muthukrishnan, Murugan (Tetrahedron Letters, 2014)
A new enantioselective synthetic route to the title compounds has been developed in a simple and practical way with high enantiopurity using commercially available starting material. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: EEHP; Epoxide; IEHP; PPAR agonists